Correlation of Planning with Budgeting Systems in Education - Nurlina, Nunung; Riduwan, Riduwan; Mufarrohah, Fatihatul (International Journal of Education, Information Technology, and Others, 2024)
This article was prepared with the aim of explaining the correlation between planning and budgeting systems in education. This writing uses qualitative methods. The results of this research conclude that planning and budgeting systems are closely related. With good budget planning, it can certainly lead to mutually desired educational goals